Neutrophil gelatinase-associated lipocalin as a biomarker for detection of early renal impairment in Iraqi patients with multiple myeloma - Alea Farhan Salman; Eham Amer Ali; Eham Amer Ali; Alaa Fadhil Alwan (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the serum neutrophil gelatinase-associated lipocalin levels in multiple myeloma patients as an indicator of disease progression. Method: The case-control study was conducted at the Clinical Biochemistry Department of the National Centre of Haematology, Mustansiriyah University, Baghdad, Iraq, from October 2020 to July 2021, amd comprised diagnosed multiple myeloma patients and healthy controls of either gender aged 40-60 years. Neutrophil gelatinase-associated lipocalin and renal functions were measured for all patients in addition to obtaining a complete history and physical examination. Data was analysed using MedCalc. Results: Of the 60 sujects, 30(50) were cases with mean age 64±2.1 years and 30(50%) were controls with mean age 60 ±3.2 years. There were 18(68%) males among the cases and 17(55%) among the controls. In the cases group, mean levels of creatinine, urea and neutrophil gelatinase-associated lipocalin were 1.62±0.85mg/dl, 55.56±28.05mg/dl and 389.39±116.12pg/mL, respectively. The corresponding values for the controls were 0.9518±0.1623mg/dl, 30.17±8.47mg/dl and 120.82±68’52pg/ml. The neutrophil gelatinase-associated lipocalin cut-off level >190pg/ml in multiple myeloma patients was strongly associated with renal impairment (p<0.001). Conclusion: Neutrophil gelatinase-associated lipocalin was found to be an accurate indicator of early kidney disease in patients with de novo multiple myeloma. Key Words: Lipocalin, Creatinine, Myeloma, Kidney, Hematology, Urea, Tumour